2002
DOI: 10.1053/beem.2002.0225
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and liver disease

Abstract: Non-alcoholic steatohepatitis (NASH) is a disease of emerging identity and importance. It is frequently associated with obesity, especially visceral fat, and is intimately related to fatty liver and markers of the insulin resistance syndrome. Both the prevalence and the severity of liver steatosis are related to body mass index, waist circumference, hyperinsulinaemia, hypertriglyceridaemia and impaired glucose tolerance or type 2 diabetes. The identification of obese patients who may progress from steatosis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 98 publications
4
87
0
2
Order By: Relevance
“…It is well documented that fatty liver is associated with obesity, and many studies have shown that increased body mass index, waist circumference and waist-hip ratio [4][5][6]13 were correlated with higher risk of fatty liver. Various types of adipose tissue (subcutaneous versus visceral and portal versus nonportal visceral fat) exhibit different metabolic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that fatty liver is associated with obesity, and many studies have shown that increased body mass index, waist circumference and waist-hip ratio [4][5][6]13 were correlated with higher risk of fatty liver. Various types of adipose tissue (subcutaneous versus visceral and portal versus nonportal visceral fat) exhibit different metabolic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Both the development of NAFLD and its progression to the more severe histology of NASH are associated with obesity and type 2 diabetes (55)(56)(57)(58)(59). NASH is known to progress to cirrhosis in up to 25% of patients (60). Serum transaminase concentrations are unreliable predictors of NAFLD, but an aspartate aminotransferase-to-alanine aminotransferase ratio Ͼ 1 has been associated with more advanced inflammation or fibrosis (61).…”
Section: Liver Diseasementioning
confidence: 99%
“…9 In addition to the increased vascular events among subjects with the MS, nonalcoholic fatty liver disease (NAFLD), an additional feature of the MS with specific hepatic insulin resistance, 10 has become the second or third commonest liver disease. 11,12 In a population study, the majority of aminotransferase elevation could not be explained by alcohol, viral hepatitis, or hemochromatosis. Rather, unexplained alanine aminotransferase (ALT) elevation was strongly associated with the adiposity and features of the MS. 13 Usually, NAFLD patients had an elevated ALT enzymatic activity, 14 but a normal ALT did not guarantee freedom from underlying steatohepatitis with advanced fibrosis.…”
Section: Introductionmentioning
confidence: 99%